Pengaruh Harmonik Akibat Pengoperasian Motor Induksi Tiga Fasa Pada Sistem Tenaga Satu Fasa - Abadi, Akbar; Meka, S Yudia; Widia, Riza (Teknik Elektro Politeknik Negeri Padang, 2023)
The research conducted focuses on analyzing the harmonic effects resulting from the operation of a three-phase induction motor in a single-phase power system and examining changes in harmonic values due to load variations using two capacitors. This study is a continuation of previous research, which only addressed the influence of a single capacitor on a three-phase induction motor in a single-phase power system, without further exploration of the extent of harmonic impact on the motor. The induction motor operates based on the principle of magnetic induction. This investigation employs a single-phase induction motor with lower power capacity compared to a three-phase induction motor. Three-phase induction motors have a small starting torque, preventing them from starting under full load. The study involves increasing the starting torque of the three-phase induction motor and operating it in a single-phase electrical power system using capacitors to improve power factor during the starting process while analyzing its harmonic effects. The research findings indicate that as the load on the motor increases, both the motor speed and harmonic current values decrease. This is evident when there is no load, and the motor speed is 1475 rpm; adding a load does not exceed this speed. The motor speed decreases as the load increases, while the presence of harmonic current values is due to the linear load, such as incandescent light bulbs. The study is conducted by enhancing the starting torque of the three-phase induction motor, imposing a significant load. The motor demonstrates more optimal and stable performance with the new method compared to the old method. Additionally, the harmonic current values with the new method are lower than those with the old method.